A study on pattern of skull fractures due to head injury - H., Vittala; Chittibabu (International Journal of Research in Medical Sciences, 2023)
Background: Skull fractures are very serious type of trauma occurring in 15% of severe head injuries, and there is a consistent association between the presence of cranial fracture and a higher incidence of intracranial lesions, neurological deficit, and poor outcome. Objectives were to study the various patterns of skull fractures and associated intracranial injuries. Methods: A prospective case series study of 50 patients with skull fractures due to head injury was selected from December 2021 to December 2022 at Srinivas Institute of Medical Sciences & Hospital, Mangalore. Out of the 50 cases, the majority were found to be co-existing with intracranial injuries, but few cases showed the presence of skull fractures alone. Among the selected patients, the clinical profile, and radiological profile was undertaken. Appropriate descriptive statistics were used to analyze the findings and to draw inferences. Results: There were 34 males and 16 females. Maximum cases were found in the age group of 31-40 years. The common cause of fracture was road traffic accident (70%) followed by assault (22%); Of the various skull fractures, linear fracture (66%) was the commonest type followed by comminuted fracture and then by depressed fracture. Common associated injuries were extradural hematoma (42%) EDH followed by intracerebral contusion (32%). Conclusions: Common causes of skull fractures are Road Traffic Accidents, assault by blunt weapons and falls from height. The commonest age group affected is 31-40 years. Skull fractures may or may not be associated with intracranial injuries.